Single‐Step Synthesis of Organometallic Molecular Squares from NR,NR′,NR′′,NR′′′‐Substituted Benzobiscarbenes - Sinha, Narayan; Roelfes, Florian; Hepp, Alexander; Hahn, F. Ekkehardt (Chemistry : a European journal, 2017)
The single‐step multicomponent self‐assembly of molecular squares featuring four bridging benzobiscarbenes and four PdII(allyl) or IrI(COD) vertices is presented. Four equivalents of the linear benzobisimidazolium salt [1](PF6)2 react with two equivalents of [Pd(allyl)Cl]2 or [IrCl(COD)]2 in the presence of Cs2CO3 to yield the tetranuclear octacarbene molecular squares [2](PF6)4 (M=Pd) and [3](PF6)4 (M=Ir), respectively. Compounds [2](PF6)4 and [3](PF6)4 feature exclusively M–carbon bonds making them the first purely organometallic molecular squares. First time! Organometallic molecular squares featuring four NR,NR‐substituted dicarbene ligands and four PdII or IrI vertices have been synthesized by a single‐step multicomponent procedure. Uniquely, the metal centers in the molecular squares feature only M−C bonds.